PENGARUH PROMOSI JABATAN TERHADAP KINERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN GANEAS KABUPATEN SUMEDANG - Sri Rini Dahliani; Dhesti Widya Nurhasanah Ningrum (Journal Of Regional Public Administration (JRPA), 2020)
The purpose of this study was to determine the effect of job promotion on the performance of the State Civil Apparatus in the Ganeas District Office of Sumedang Regency. In this study, researchers used a quantitative research methodology with descriptive research type. And researchers used a saturated sampling technique with a sample of 18 people consisting of the State Civil Apparatus in the Ganeas District Office of Sumedang Regency. Data collection techniques are carried out by means of library studies and field studies which include observation, and questionnaire distribution. Then the data processing technique is done by calculating the validity test, reliability test, percentage test, correlation test, significance test and test the coefficient of determination. The results of this study, researchers can describe that the influence of job promotion on the performance of the state civil servants reached 82.99%. The remaining 17.01% is influenced by other factors not examined by researchers called epsilon factor.